2016
DOI: 10.11114/jets.v4i8.1538
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service Teachers Identify Connections between Teaching-learning and Literacy Strategies

Abstract: This study explores the transformation of pre-service teachers in their attainment of effective teaching skills. Pre-service teachers learn about the learning-to-read process and implementations of component skills of teaching reading within the practicum. More importantly, pre-service teachers achieve a meaningful understanding of the declarative, procedural and strategic knowledge of working with struggling readers as well as the merits, utilities and appropriate applications of important literacy skills. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Analysis of the data suggested that both Rick and Michaela were ready and motivated to learn from self-directed approaches, and they were genuinely interested in learning how to apply proven effective SLA strategies because these new skills were relevant to their current roles. With specific and immediate feedback during the lesson demonstrations, novice teachers can make explicit connections between the study of content pedagogy and enactment of the lesson, promote quality language learning, acquire content knowledge through metalinguistic techniques, and bolster transfer (Liu et al, 2016).…”
Section: Importance Of Sense-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the data suggested that both Rick and Michaela were ready and motivated to learn from self-directed approaches, and they were genuinely interested in learning how to apply proven effective SLA strategies because these new skills were relevant to their current roles. With specific and immediate feedback during the lesson demonstrations, novice teachers can make explicit connections between the study of content pedagogy and enactment of the lesson, promote quality language learning, acquire content knowledge through metalinguistic techniques, and bolster transfer (Liu et al, 2016).…”
Section: Importance Of Sense-makingmentioning
confidence: 99%
“…TCs appreciate think-time to reflect and revise their own teaching-learning approaches. They can benefit from individualized coaching, including the use of think-aloud in the context of how to make on-the-go instructional decisions and make the invisible learning visible (Liu et al, 2016;Won et al, 2019). This study is important because it provides a platform that shows the power of coaching in terms of helping TCs to engage in instructional High-Leverage Practices that make teachinglearning experiences more inclusive and impactful.…”
Section: Significancementioning
confidence: 99%
“…Teaching is a skill where much of the learning of enacting the skill occurs in practicing those skills within a highly analogous yet more structured situation. Thus, many preservice teacher training programs emphasize reflection combined with practice [10]- [12]. While these programs aim to prepare teachers for K-12 education, at least within the US, many lessons can be adapted to the academic preparatory process.…”
Section: Faculty Apprenticeship As a Form Of Student Teachingmentioning
confidence: 99%